A07 The impact of urban structure on mental health in Turin: the importance of public transport accessibility. Issue 2 (June 2015) - Melis, Giulia; Marra, Giulia; Ferracin, Elisa; Gelormino, Elena; Costa, Giuseppe
Abstract: Background: Mental health has a relevant burden on the health of populations. Common mental health disorders (anxiety and non-psychotic depression) are well associated to socioeconomic individual and neighborhood characteristics, but little is known about the influence of urban structure. Methods: We analyzed among the 900, 000 inhabitants of Turin (Northwest Italy) the association between the fact of living in areas with different urban structure characteristics (density, accessibility by public transport, accessibility to services, green and public spaces) and first consumption of antidepressants (atc: N06A), as indicator of depressive symptoms. Multilevel Poisson regression models were used to estimate this association (relative index of inequality), adjusted by individual socio-demographic variables (education, housing tenure, employment) and contextual social environment variables (social and physical disorder, crime rates). Data used are referred to 2006-2008, and come from open sources of the municipality, police register census and the Turin Longitudinal Study (TLS) - a census based cohort study following up prospectively the mortality and morbidity of the population. Results: As expected, individual socio-demographic variables show the strongest association with antidepressive drug consumption: migrants consume less, while unemployed and less educated consume more. Most of the built environment indicators are weakly associated to mental health, but accessibility. A good public transport service seems to be an important protective factor, which turns out to be significant for older men (50-65) and women of all ages. Urban density is significant only if considered as an alternative to accessibility. Conclusions: Evidence suggests that the structure of built environment has an effect on mental health of people who spend more time in it: women, as well as men over 50, independently from the socioeconomic individual and contextual characteristic. A good accessibility with public transport, as well as a dense urban structure (vs sprawl), can contribute to reduce the risk of depression, especially for women and retired people, giving them the opportunity to move around, satisfy their needs and have an active social life.